The fundamentals of posture’s biomechanics and their implications on the performance of the flute (Per Musi, 2015)
The systematic practice of a musical instrument is not a simple issue and involves physical and emotional demands which are difficult to understand by those who are not engaged with this activity. Researchers recognize that such demand may significantly affect the musician’s career. Important studies have been conducted on this subject. Given this context, this paper presents a study of the fundamentals of the posture’s biomechanics and their implications on the performance of the flute. From the concept of normal posture (gravity of body center, the static muscle, and the normal posture - standing and seated), the fundamental aspects of the posture’s biomechanics during flute’s performance, and the inherent postural changes in this performance were considered.